2009
DOI: 10.1155/2009/937352
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Resistance

Abstract: The development of adverse cardiovascular events despite aspirin use has established an interest in a possible resistance to the drug. Several definitions have been set and various laboratory testing modalities are available. This has led to a wide range of prevalence reports in different clinical entities. The etiologic mechanism has been related to clinical, genetic, and other miscellaneous factors. The clinical implications of this phenomenon are significant and warrant concern. Management strategies are cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 94 publications
1
26
0
3
Order By: Relevance
“…Resistance to dual antiplatelet therapy was found in 9% of patients, a finding that is in accordance with studies in which aspirin resistance was found in 6% -27% and clopidogrel resistance was found in 15% -30% of patients [17][18][19][20][21] . However, the results of multiplate aggregometry did not differ significantly between patients with and without new ischemic lesions in the brain in the present study.…”
Section: Statistical Analysessupporting
confidence: 89%
See 1 more Smart Citation
“…Resistance to dual antiplatelet therapy was found in 9% of patients, a finding that is in accordance with studies in which aspirin resistance was found in 6% -27% and clopidogrel resistance was found in 15% -30% of patients [17][18][19][20][21] . However, the results of multiplate aggregometry did not differ significantly between patients with and without new ischemic lesions in the brain in the present study.…”
Section: Statistical Analysessupporting
confidence: 89%
“…Low efficacy of resistance to antiplatelet therapy could increase the risk of new ischemic lesions in the brain during and after CAS 16) . Scholars have reported a prevalence of resistance of 6% -27% in different populations for acetylsalicylic acid 17,18) and of 15% -30% for clopidogrel [19][20][21] . Selection of patients carrying a high risk of periprocedural ischemic infarction could decrease the risk of stroke, transient ischemic attack (TIA), and subsequent cognitive decline in patients undergoing CAS.…”
Section: Mrimentioning
confidence: 99%
“…ibuprofen, indomethacin) may interfere with aspirin's anti-thrombotic effect by blocking its docking site on COX-1 [31]. Proton pump inhibitors (PPIs), that suppress gastric acid secretion, may reduce the bioavailability of aspirin due to inactivation of the drug by gastrointestinal mucosal esterases thus reducing its absorption [32]. PPIs are substrates and competitive inhibitors of CYP2C19, the hepatic isoenzyme that plays a major role in the activation of clopidogrel.…”
Section: Reduced Bioavailability Of Anti-platelet Drugsmentioning
confidence: 99%
“…A concept of "aspirin resistance (AR)" describes the inability of aspirin to thromboxane (TX) biosynthesis and produces an anticipated effect on one or more in vitro tests of platelet function [2]. Clinically, aspirin resistant patients still develop adverse vascular events despite aspirin intake [3].…”
Section: Introductionmentioning
confidence: 99%